2006
DOI: 10.1111/j.1399-302x.2006.00314.x
|View full text |Cite
|
Sign up to set email alerts
|

Actinobacillus actinomycetemcomitans lipopolysaccharide induces interleukin‐6 expression through multiple mitogen‐activated protein kinase pathways in periodontal ligament fibroblasts

Abstract: Actinobacillus actinomycetemcomitans plays a major role in the pathogenesis of aggressive periodontitis. Lipopolysaccharide (LPS) derived from A. actinomycetemcomitans is a key factor in inflammatory cytokine generation within periodontal tissues. In this study, we identify major mitogen-activated protein kinase (MAPK) signaling pathways induced by A. actinomycetemcomitans LPS, Escherichia coli LPS and interleukin-1beta (IL-1beta) in a murine periodontal ligament (mPDL) fibroblast cell line. Immunoblot analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
59
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 35 publications
1
59
0
1
Order By: Relevance
“…Although E. coli LPS used to provoke in vivo periodontal tissue damage is not periodontal pathogen, it has the same kind of responses as A.a. LPS. 32 In addition, periodontal tissue destruction caused by topical application of E. coli LPS into the rat gingival sulcus is well established. [7][8][9][10][11] In our animal model, typical B-cell lesion-like human chronic periodontitis did not develop.…”
Section: Discussionmentioning
confidence: 94%
“…Although E. coli LPS used to provoke in vivo periodontal tissue damage is not periodontal pathogen, it has the same kind of responses as A.a. LPS. 32 In addition, periodontal tissue destruction caused by topical application of E. coli LPS into the rat gingival sulcus is well established. [7][8][9][10][11] In our animal model, typical B-cell lesion-like human chronic periodontitis did not develop.…”
Section: Discussionmentioning
confidence: 94%
“…A. actinomycetemcomitans is a gram-negative, facultative, anaerobic, nonspore-forming, and nonmotile coccobacillus. Previous investigations have suggested that A. actinomycetemcomitans produces a variety of virulence factors including the leukotoxin (Ltx) (Lally et al, 1997;Korostoff et al, 1998), cytolethal distending toxin (Cdt) (Shenker et al, 1999(Shenker et al, , 2001, and lipopolysaccharide (Lps) (Kiley and Holt, 1980;Patil et al, 2006). A. actinomycetemcomitans also expresses heat shock protein GroEL (Hsp64) (Koga et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…8) Together these transcription factors control the activation of gene promoters containing AP-1, nuclear factor-kappa B (NF-kB), and C/EBP (ccAAT enhances binding protein) elements to control the expression of target genes resulting inflammatory responses including MMPs. 9) A number of strategies have been designed to block the excess production of MMPs by periodontal host cells to treat periodontitis. Inhibition of MMPs via blocking enzymatic activity offers a straightforward therapeutic target in periodontal disease therapy.…”
mentioning
confidence: 99%